Komunikasi Partisipatori Pada Program Pemberdayaan Masyarakat Dalam Penanganan TB - Maya May Syarah; Mari Rahmawati (Universitas Bina Sarana Informatika, 2017)
The high number of Tuberculosis (TB) in Indonesia made health development as main part of government’s mission in National Middle Term of Plan (RPJMN). Based on that mission, The Health Ministry formulated some strategies and one of them is to increase the community empowerment, private and civil society through national cooperation and global. The successful of one assisting activity for community empowerment will be determined by communication which participative. Community program of TB Care Aisyiyah is one program that moved to realize the health infrastructure of non-governmental and dynamic of social group who able independently improved TB problem in Indonesia. Aisyiyah as autonomy muslim women's organization, special from Muhammadiyah was selected being main coordinator of fund receiver from Global fund represents civil society. The author used mixed method and non-probability sampling with purposive sampling, the sample which was selected is Kalianyar District where associated in KPT of West Jakarta. This research aimed to explain participatory communication which occurred on Program of people empowerment for TB handling in Aisyiyah, then to analyze the correlation of determination factors among participatory communication on that program. The research result has shown participatory communication viewed on some communication forums which were conducted by that program. In forum where consist of patients, PMO, Cadres and the facilitator who associated with KPT of West Jakarta. Those communication forums used diversities such as religion differentiation, ethnics, economic class, culture, gender and ideology to reach joint purpose of TB disease handling. At some meetings, the dialogue occurred as a special identity from participatory communication. The research result also showed the real correlation occurred among determination factors of participatory communication with community program of TB Care Aisyiyah.